2019
DOI: 10.12688/f1000research.20399.1
|View full text |Cite
|
Sign up to set email alerts
|

The development of mouthwashes without anti-gonococcal activity for controlled clinical trials: an in vitro study

Abstract: Background: The oropharynx plays a major role in the development and spread of antimicrobial resistant Neisseria gonorrhoeae among men who have sex with men. Trials are currently assessing the efficacy of bactericidal mouthwashes as possible therapeutic or preventive options against these pharyngeal gonococcal infections. Controlled clinical trials require the use of a placebo mouthwash without anti-gonococcal activity. So far, no such mouthwash has been described. We describe the development of a mouthwash fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Importantly, the one commercially available alcohol-containing mouthwash included in this study (Listerine Cool Mint with 22% alcohol) demonstrated complete inhibition of N. gonorrhoeae in both the PBS and saliva matrices at all time points, likely due to the inhibitory activity of the other antibacterial constituents in the preparation. These findings are consistent with earlier studies ( 6 , 7 ). Further studies would benefit from the inclusion of additional commercially available alcohol-containing mouthwashes to assess the impact of saliva on the inhibition of N. gonorrhoeae in these preparations.…”
Section: Introductionsupporting
confidence: 94%
See 1 more Smart Citation
“…Importantly, the one commercially available alcohol-containing mouthwash included in this study (Listerine Cool Mint with 22% alcohol) demonstrated complete inhibition of N. gonorrhoeae in both the PBS and saliva matrices at all time points, likely due to the inhibitory activity of the other antibacterial constituents in the preparation. These findings are consistent with earlier studies ( 6 , 7 ). Further studies would benefit from the inclusion of additional commercially available alcohol-containing mouthwashes to assess the impact of saliva on the inhibition of N. gonorrhoeae in these preparations.…”
Section: Introductionsupporting
confidence: 94%
“…Some mouthwashes have in vitro bactericidal activity against N. gonorrhoeae ( 6 , 7 ). However, two recent randomized controlled trials using mouthwash did not demonstrate a difference in the incidence of oropharyngeal gonorrhea in individuals receiving a daily preventative mouthwash over a 3-month period ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…35 A retrospective case-control study in New Zealand has shown that the MeNZB vaccine reduced the incidence of gonorrhoea by 31% over 10 years; 36 however, the effectiveness against oropharyngeal gonorrhoea is unknown. Additionally, the use of antiseptic mouthwash has also been proposed as a novel intervention for gonorrhoea; 29,[37][38][39][40][41] however, several clinical trials have demonstrated that daily use of antiseptic mouthwash fails to prevent gonorrhoea acquisition and is an ineffective prevention and treatment. [42][43][44][45][46] Given that kissing practices are common, a public health message is important to reinforce the awareness that gonorrhoea can be transmitted through kissing.…”
Section: Discussionmentioning
confidence: 99%
“…Although experiments in mice have suggested that chlorhexidine might effectively prevent genital Ng infection, 12 data for preventive or therapeutic efficacy on human oropharyngeal gonorrhea are lacking. Nevertheless, chlorhexidine's strong in vitro bactericidal effect suggests that it could be more effective than Listerine in killing Ng in the oropharynx 6,8,13,14 …”
mentioning
confidence: 99%
“…[1][2][3] As a consequence, several authors have proposed that antiseptic mouthwashes may be used to prevent or treat oropharyngeal gonorrhea. 1,4,5 In vitro studies have established that Ng is highly susceptible to killing by mouthwashes such as Listerine 6,7 and chlorhexidine, [8][9][10] and a randomized controlled trial in men with culture-positive oropharyngeal gonorrhea found that Ng could not be cultured in a significant proportion of men 5 minutes after a single gargling session with Listerine. 7 Despite these initial encouraging results, 3 randomized clinical trials have found that Listerine failed to prevent (PReGo 4 and OMEGA1 11 ) or treat (OMEGA2 5 ) oropharyngeal gonorrhea.…”
mentioning
confidence: 99%